2020
DOI: 10.1515/psr-2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Domains and domain walls in multiferroics

Abstract: Multiferroics are materials combining several ferroic orders, such as ferroelectricity, ferro- (or antiferro-) magnetism, ferroelasticity and ferrotoroidicity. They are of interest both from a fundamental perspective, as they have multiple (coupled) non-linear functional responses providing a veritable myriad of correlated phenomena, and because of the opportunity to apply these functionalities for new device applications. One application is, for instance, in non-volatile memory, which has led to special atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 175 publications
(255 reference statements)
1
49
0
1
Order By: Relevance
“…However, this will not happen in the near future without substantial efforts in bulk material synthesis, characterization and modeling. The new possibilities for electric and magnetic domain imaging, summarized in two recent reviews [64,119], may contribute to these efforts, hopefully helping to transfer the most promising materials and phenomena to thin films. In parallel, it is important to pursue the investigation of other near-RT bulk multiferroic materials (such as CuO [120] and the ferrimagnetic family Ga2-xFexO3 [121,122]), and materials such as -Fe2O3 where RT multiferroicity has only been reported in nanocrystalline or thin-film form [123].…”
Section: Future Trends In Single-phase Magnetoelectricsmentioning
confidence: 99%
“…However, this will not happen in the near future without substantial efforts in bulk material synthesis, characterization and modeling. The new possibilities for electric and magnetic domain imaging, summarized in two recent reviews [64,119], may contribute to these efforts, hopefully helping to transfer the most promising materials and phenomena to thin films. In parallel, it is important to pursue the investigation of other near-RT bulk multiferroic materials (such as CuO [120] and the ferrimagnetic family Ga2-xFexO3 [121,122]), and materials such as -Fe2O3 where RT multiferroicity has only been reported in nanocrystalline or thin-film form [123].…”
Section: Future Trends In Single-phase Magnetoelectricsmentioning
confidence: 99%
“…Seidel et al first directly observe the conductivity at DWs in BFO; they found that 180°and 109°DWs in multiferroic BiFeO 3 thin films are conductive at room temperature while the 71°DWs are non-conducting 123 . Numerous studies on DW conductivity have been carried out since then 129,130 . One mechanism of non-charged DW conductivity is from the inhomogeneous elastic strains.…”
Section: The Polarization-induced Anisotropic Conductance Of Noncharged Dwsmentioning
confidence: 99%
“…A second development relates to the current in domain walls and associated chemical changes. Ever since the discovery of superconductivity in domain walls (Aird and Salje 1998) and subsequent studies of highly conducting walls (Seidel et al 2010), the concept of domain wall electronics was developed rapidly and was reviewed by Catalan et al (2012) and Evans et al (2020).…”
Section: Moving Twin Boundariesmentioning
confidence: 99%